ANALYSIS RISK FACTORS AND PREVENTION MANAGEMENT STUNTING - Syakur, Rosdiana; Susanti, Rahma Sri; Sakaria, Jumeria; Usman, Jusman; Rosdiana, Rosdiana (Homes Journal: Hospital Management Studies Journal, 2024)
Background: Stunting is a condition where there is failure to grow in children under five years old (babies under five years) caused by chronic malnutrition so that the child is too short for his age. Short (stunted) toddlers are influenced by many factors such as Low birth weight (LBW), exclusive breastfeeding, infectious diseases, and completeness of basic immunization. Objective: The aim of this study was to analyze the risk factors for stunting in toddlers aged 24 months-60 months at the Mandai Community Health Center, Maros Regency in 2023. Method: The type of research used was observational with an analytical research type in the case control study approach, namely remotely analyzing subjects in the form of 68 cases identified as stunting and comparing them with a control group of 68 who did not experience stunting. Data were processed and analyzed using the Odds Ratio (OR) test in the SPSS program. Result: The results of this study show that there is an OR value for birth weight of 22.50, an OR value for exclusive breastfeeding of 17.05, an OR value for infectious diseases of 12.90, and completeness of basic immunization of 18.85. Conclusion: From the above data it is concluded that Weight Birth of babies, exclusive breastfeeding, infectious diseases and completeness of basic immunization are risk factors for the incidence of stunting in toddlers in the working area of ​​the Mandai Community Health Center, Maros Regency .